Anthropometric assessment of the dehydration in high level Rugby athletes - Rossi, L.; Guerreiro dos Santos, F.; Leao, L. (Brazilian Journal of Biomotricity, 2013)
Rugby is a growing sport in Brazil, with few academic studies, particularly on anthropometry and dehydration risk. We evaluated high level male rugby athletes to determine their anthropometric profile and degree of dehydration during a competitive match. We registered the body mass (BM: kg) and height (H: m), evaluated the body fat percentage (%BF), sweating rate (SR: mL/min) e percentage of water loss (%WL). The athletes had ages between 26.3 ± 5.6 years, 1.81 ± 0.06m e %BF 14.9 ± 4.2%. There was statistically significant between pre and post training BM (p<0.02). Although the %WL reduction was <2%, this value was determined to be critical for performance. Even with a low dehydration risk, studies on the professional rugby leagues point that, due to the intermittent characteristics of the sports, there may be losses in physical and cognitive performance in high level athletes, making desirable the monitoring of water loss in order to replace liquids lost during trainings and competitions.